SURGICAL MANAGEMENT OF IRREDUCIBLE ATLANTO-AXIAL DISLOCATION WITH OS ODONTOIDEUM AND KLIPPEL-FEIL SYNDROME - Akhtar, Muhammad Shaheer; Riaz Ur Rehman,; Irfan Ali, (Journal of Ayub Medical College Abbottabad, 2022)
Klippel-Feil syndrome (KFS) is the congenital fusion of two or more cervical vertebrae which is often associated with various other abnormalities in the cervical spine. Involvement the upper cervical segments leads to atlanto-axial instability which manifests as progressive neurological symptoms due to compression on the spinal cord. These cases pose a surgical challenge due the abnormal and unique anatomy of each patient. A 37-year-old patient presented with neck pain and cervical myelopathy due to a posterior subluxation of C2-3 fused segment over C4-6 fused segment. The patient had an os odontoideum, incomplete posterior arch of C1, anomalous course of vertebral artery and C3 hemi-vertebra. The patient was successfully managed with transoral odontoidectomy and occipeto-cervical fusion. Irreducible atlanto-axial dislocation in a patient with an abnormal upper cervical spine anatomy may require transoral decompression followed by posterior fusion.